Psychometrics of the Persian version of the COVID-19-related health literacy in the Iranian population - Torkian, Samaneh; Ebrahimi, Fatemeh; Shahnazi, Hossein; Rashti, Roya; Emami, Mahasti; Maracy, Mohammad Reza (Frontiers in Public Health, 2023)
Background: Since the outbreak of the COVID-19 epidemic, information dissemination has increased rapidly. Promoting health literacy is currently crucial to prepare people to respond quickly to situations such as the COVID-19 pandemic. Due to the health literacy importance in this critical situation, we are looking for a questionnaire to measure COVID-19 health literacy. The COVID-19 Germany Health Literacy Questionnaire is an excellent tool so the study aimed to create a culture and validity of this questionnaire for the Iranian population. Methods: In this validation study, 880 samples were enrolled via a convenient sampling method. The questionnaire was translated through a backward forwarding procedure. Confirmatory factor analysis (CFA) and exploratory factor analysis (EFA) were employed for Persian version validity. McDonald's omega (Ω), Cronbach’s alpha, and average inter-item Correlation (AIC) coefficients were assessed reliability. Results: Using EFA on the random half sample (n = 440), the EFA indicated that the scale had four factors: accessing, understanding, appraising, and applying health-related information in the COVID-19 pandemic context, which explained 59.3% of the total variance. CFA was used for the sample second part (n = 440), to evaluate the goodness of fit of the 4-factor solution. CFA showed the model fit. All indices RMSEA = 0.067, CFI = 0.934, IFI = 0.934, PCFI = 0.772, PNFI = 0.747, CMIN/DF = 2.972 confirmed the model fit. Discriminant and convergent validity of the HLS-COVID-Q22 were confirmed. The McDonald's omega and Cronbach’s alpha were very good (α and Ω >0.80). Conclusion: The Persian version of the HLS-COVID-Q20 had acceptable psychometric properties and is applicable to measure COVID-19 health literacy.